The effectiveness and complexity of interventions targeting sedentary behaviour across the lifespan: a systematic review and meta-analysis - Nicole E. Blackburn; Jason J. Wilson; Ilona I. McMullan; Paolo Caserotti; Maria Giné-Garriga; Katharina Wirth; Laura Coll-Planas; Sergi Blancafort Alias; Marta Roqué; Manuela Deidda; Andrew T. Kunzmann; Dhayana Dallmeier; et al. (BMC, 2020)
Abstract Background Evidence suggests that sedentary behaviour (SB) is associated with poor health outcomes. SB at any age may have significant consequences for health and well-being and interventions targeting SB are accumulating. Therefore, the need to review the effects of multicomponent, complex interventions that incorporate effective strategies to reduce SB are essential. Methods A systematic review and meta-analysis were conducted investigating the impact of interventions targeting SB across the lifespan. Six databases were searched and two review authors independently screened studies for eligibility, completed data extraction and assessed the risk of bias and complexity of each of the included studies. Results A total of 77 adult studies (n=62, RCTs) and 84 studies (n=62, RCTs) in children were included. The findings demonstrated that interventions in adults when compared to active controls resulted in non-significant reductions in SB, although when compared to inactive controls significant reductions were found in both the short (MD -56.86; 95%CI -74.10, -39.63; n=4632; I2 83%) and medium-to-long term (MD -20.14; 95%CI -34.13, -6.16; n=4537; I2 65%). The findings demonstrated that interventions in children when compared to active controls may lead to relevant reductions in daily sedentary time in the short-term (MD -59.90; 95%CI -102.16, -17.65; n=267; I2 86%), while interventions in children when compared to inactive controls may lead to relevant reductions in the short-term (MD -25.86; 95%CI -40.77, -10.96; n=9480; I2 98%) and medium-to-long term (MD -14.02; 95%CI -19.49, -8.55; n=41,138; I2 98%). The assessment of complexity suggested that interventions may need to be suitably complex to address the challenges of a complex behaviour such as SB, but demonstrated that a higher complexity score is not necessarily associated with better outcomes in terms of sustained long-term changes. Conclusions Interventions targeting reductions in SB have been shown to be successful, especially environmental interventions in both children and adults. More needs to be known about how best to optimise intervention effects. Future intervention studies should apply more rigorous methods to improve research quality, considering larger sample sizes, randomised controlled designs and valid and reliable measures of SB.